2017
DOI: 10.3389/fimmu.2017.00249
|View full text |Cite
|
Sign up to set email alerts
|

Anopheles stephensi Heme Peroxidase HPX15 Suppresses Midgut Immunity to Support Plasmodium Development

Abstract: The heme peroxidase HPX15 is an evolutionary conserved anopheline lineage-specific gene. Previously, we found that this gene is present in the genome of 19 worldwide distributed different species of Anopheles mosquito and its orthologs are absent in other mosquitoes, insects, or human. In addition, 65–99% amino acid identity among these 19 orthologs permitted us to hypothesize that the functional aspects of this gene might be also conserved in different anophelines. In this study, we found that Anopheles steph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 32 publications
2
12
0
Order By: Relevance
“…These observations further corroborate and support the idea that the down-regulation of salivary apyrase is crucial to enhances host attraction of the Plasmodium-infected than un-infected mosquitoes (46). Recently, hemeperoxidase homolog HPX15, has been suggested to act as an agonist and likely favor the survival of endogenous gut-bacterial population as well as Plasmodium parasite, by the formation of crosslinked mucin barrier on the luminal side of the midgut (40). Elevation of salivary AsHPX12 mRNA level after 24hrs of blood-feeding and consistent up-regulation in response to salivary invaded P. vivax sporozoites, together indicate that AsHPX12 may have a dual role in the management of salivary gland homeostasis and long term survival of stored sporozoites.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…These observations further corroborate and support the idea that the down-regulation of salivary apyrase is crucial to enhances host attraction of the Plasmodium-infected than un-infected mosquitoes (46). Recently, hemeperoxidase homolog HPX15, has been suggested to act as an agonist and likely favor the survival of endogenous gut-bacterial population as well as Plasmodium parasite, by the formation of crosslinked mucin barrier on the luminal side of the midgut (40). Elevation of salivary AsHPX12 mRNA level after 24hrs of blood-feeding and consistent up-regulation in response to salivary invaded P. vivax sporozoites, together indicate that AsHPX12 may have a dual role in the management of salivary gland homeostasis and long term survival of stored sporozoites.…”
Section: Discussionsupporting
confidence: 80%
“…5a). Since, earlier studies demonstrate that a gut-specific AsHPX15, may favor Plasmodium development by the formation of a crosslinking mucin layer at the luminal side of the gut epithelium (40), we also tested whether Plasmodium infection also modulates HPX12 responses in the mosquito salivary glands. Detailed transcriptional profiling showed a gradual elevation of AsHPX12 level in response to salivary invaded P. vivax sporozoite infection (Fig.…”
Section: Ashpx-12 Regulates Pre-blood Meal Associated Behavioral Respmentioning
confidence: 99%
“…In fact, NOS is a well-documented antiplasmodial molecule and the ookinetes must migrate out of the midgut cell before they are damaged by the action of this protein (Han and Barillas-Mury, 2002; Kumar et al, 2004, 2010; Gupta et al, 2005; Kajla et al, 2017). Thus, it might be possible that the early event of epithelial invasion by the ookinetes is also negatively affected in AsApoLp-III silenced midguts due to the toxic effect of NOS.…”
Section: Resultsmentioning
confidence: 99%
“…stephensi to Plasmodium infection by preventing the recognition of the parasite. They found that silencing HPX15 resulted in increased expression of NOS and parasite clearance [173]. These studies suggest that modulation of inducible NOS levels or activity can enhance refractoriness of mosquitoes to parasite thus preventing malaria transmission.…”
Section: Metabolic Proteins and Immune Response To Plasmodium Infectimentioning
confidence: 93%
“…Also, they noted that inhibiting NOS reduced parasite clearance while providing L-arginine (a substrate required by the enzyme for the synthesis of nitric oxide), enhanced parasite clearance [172]. Kajla et al [173] discovered that heme peroxidase 15 (HPX 15) suppressed immune response of An. stephensi to Plasmodium infection by preventing the recognition of the parasite.…”
Section: Metabolic Proteins and Immune Response To Plasmodium Infectimentioning
confidence: 99%